2008
DOI: 10.1007/s00056-008-0745-2
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial Findings in Conjunction with Infantile Cerebral Paralysis in Adults of Two Different Age Groups – a Cross-sectional Study

Abstract: We observed an overall correlation between the frequency of malocclusions and severity of mental retardation. The amount of orthodontic treatment was significantly higher in the younger group (32.3%) than the older group (0%). In diagnostic terms, orthodontic treatment should follow the general guidelines, namely, the recommendation of removable devices as treatment appliances, and multidisciplinarily speaking, modified sequences of myofunctional therapy in consideration of the individual compliance prognosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
2
2
1
Order By: Relevance
“…These discrepancies are in strong contrast to the increased overjet described by all authors among patients with CP versus the controls (8,10,13,14,24). In our study, increased overjet was seen in 45.5% of the cases, which is high compared with the normal population, where the reported prevalence is 8.5% (22).…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…These discrepancies are in strong contrast to the increased overjet described by all authors among patients with CP versus the controls (8,10,13,14,24). In our study, increased overjet was seen in 45.5% of the cases, which is high compared with the normal population, where the reported prevalence is 8.5% (22).…”
Section: Discussioncontrasting
confidence: 92%
“…In coincidence with some studies (24), we found molar class II to account for 40% of the sample, though other authors have reported prevalences as diverse as 75.85% and 26.4% (8,10). These discrepancies are in strong contrast to the increased overjet described by all authors among patients with CP versus the controls (8,10,13,14,24).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the presented case a caries‐free dentition was found without the need for conservative therapy. The dental status corresponds with information from other case reports and study data, which also described mostly a caries‐free dentition or lower DMFT‐values in CP patients compared to other types of disabilities or to the normal population 18,22,23 . An orthodontic treatment was primarily necessary which had to be supported by a structured dental prophylaxis and behavioral concept.…”
Section: Discussionsupporting
confidence: 65%
“…Several studies recorded that patients with CP have a high prevalence of dental problems and malocclusions such as class II and therefore require orthodontic treatment 8,10,15–18 . Partly this may be a consequence of the primary physical impairment of patients with CP due to hyper‐ or hypofunction of muscle tone (sleep, spasticity) depending on the severity 19,20 .…”
Section: Discussionmentioning
confidence: 99%